An indirect treatment comparison of the efficacy of insulin degludec/liraglutide (IDegLira) and insulin glargine/lixisenatide (iGlarLixi) in patients with type 2 diabetes uncontrolled on basal insulin. (3rd April 2018) - Evans, Marc; Billings, Liana K.; Håkan-Bloch, Jonas; Slothuus, Ulla; Abrahamsen, Trine J.; Andersen, Andreas; Jansen, Jeroen P.
Abstract: Aims: To obtain estimates of the relative treatment effects between insulin degludec/liraglutide (IDegLira) and insulin glargine U100/lixisenatide (iGlarLixi) in patients with type 2 diabetes mellitus (T2DM) uncontrolled on basal insulin therapy. Materials and methods: Data from phase 3 trials providing evidence for estimating the relative efficacy and safety of IDegLira vs iGlarLixi in patients uncontrolled on basal insulin-only regimens were used in this analysis. Outcomes of interest were changes in HbA1c, body weight and insulin dose, and rate ratio of hypoglycemia. The indirect comparison of the reported trial findings followed the principles of Bucher et al. Results: IDegLira was estimated to provide a 0.44 [95% CI = 0.17–0.71] %-point reduction in HbA1c compared with iGlarLixi. Body weight was reduced by 1.42 [95% CI = 0.35–2.50] kg with IDegLira compared with iGlarLixi. Insulin dose was comparable between the two interventions. The rate of severe or blood glucose-confirmed (self-measured plasma glucose [SMPG] ≤ 3.1 mmol/L) hypoglycemia with IDegLira was approximately half that of iGlarLixi (rate ratio = 0.51 [95% CI = 0.29–0.90]). However, using the American Diabetes Association definition of documented symptomatic hypoglycemia (SMPG ≤3.9 mmol/L) the rate was comparable between the two treatments (rate ratio = 1.07 [95% CI = 0.90–1.28]). Limitations: The assumptions made in the indirect comparison and differences between the included trials in baseline HbA1c levels, previous use of sulfonylureas, definitions of hypoglycemia, presence or absence of run-in period, the different duration of the trials, and the cross-over design of one of the trials. Conclusions: The results of this indirect treatment comparison demonstrate that, among patients with T2DM uncontrolled on basal insulin, treatment with IDegLira results in a greater reduction of HbA1c and a greater reduction in body weight compared with iGlarLixi at similar insulin doses.